The Role of Zakat on Economic Growth: Modification of the Mathematical Model from an Islamic Economic Perspective - Yusuf, Muhammad Zulfikar (El-Barka, 2025)
Zakat is seen as a financial instrument that minimizes economic inequality and distributes wealth from the rich to the poor and needy. Empirical facts show that zakat can stimulate economic growth, increase consumption, investment and government spending. However, the role of zakat variable is often overlooked, especially in the context of mathematical model of economic growth. Therefore, this research seeks to evaluate the mathematical model of economic growth and modify it by involving zakat variable. It is important to conduct this research to measure the socio-economic impacts produced by zakat and analyze economic growth more comprehensively. The method used in this research is conceptual approach with library research. This research offers a mathematical model involving zakat variable in economic growth. The model offered is Y = C + I + G + Z + (X – M), where Z is the zakat. Thus, adding zakat variable to the mathematical model needs to be implemented to read economic dynamics comprehensively, especially in Muslim majority country such as Indonesia. The implications of this research play an important role in providing decision recommendations for policymakers and zakat institutions.